2015
DOI: 10.1371/journal.pone.0143260
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive MicroRNA Expression Profile Related to Hypoxia Adaptation in the Tibetan Pig

Abstract: Tibetan pigs live between 2500 and 4300 m above sea level on the Tibetan Plateau, and are better adapted to hypoxia than lowland pigs. MicroRNAs (miRNAs) are involved in a wide variety of cellular processes; however, their regulatory role in hypoxia adaptation remains unclear. In this study, miRNA-seq was used to identify differentially expressed miRNAs (DE miRNAs) in the cardiac muscle of Tibetan and Yorkshire pigs, which were both raised in high elevation environments. We obtained 108 M clean reads and 372 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Studies have shown that the nutritional characteristics, flavor, and quality of meat from Tibetan pigs are different from those of common pigs (Mi, Li, et al, ; Mi, Shang, et al, ; Zhang et al, ). Therefore, the special quality formation mechanism of Tibetan pork presents an important scientific question and has not yet been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the nutritional characteristics, flavor, and quality of meat from Tibetan pigs are different from those of common pigs (Mi, Li, et al, ; Mi, Shang, et al, ; Zhang et al, ). Therefore, the special quality formation mechanism of Tibetan pork presents an important scientific question and has not yet been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…According to a previous study, miRNAs related to hypoxia exhibit significant changes in Tibetan pigs compared to other species [30]. To date, very few miRNAs have been reported to play important roles in avian adaptation to hypoxia at high altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling is an important pathway by which hypoxia promotes tumorigenesis by suppressing the transactivation activity of p300 [45], and thus plays an important role in tumor growth and transformation, depending on angiogenesis and alterations in glucose metabolism [46]. As shown in the study by Zhang et al [30]. , the MAPK signaling pathway regulates adaptations to hypoxia in the Tibetan pig.…”
Section: Discussionmentioning
confidence: 99%
“…Tibetan pigs are typical high-altitude pig breeds living on the Qinghai-Tibet Plateau, and are vital to the lives of Tibetan people [1]. The main producing areas of Hezuo Tibetan pigs are located in the southwestern of Gansu province in Gannan Tibetan Autonomous Prefecture, on the northeast edge of the Qinghai-Tibet Plateau, with an average elevation of about 3000 meters [2]. Hezuo Tibetan pigs belong to a group of Tibetan pigs, which can adapt to the harsh plateau environment and feeding conditions, mainly relying on grazing for their livelihood [3].…”
Section: Introductionmentioning
confidence: 99%